Membandingkan Konsep Islam Keindonesiaan dengan Islam Nusantara dalam Kerangka Pluralisme - M Faizal Zaky Mubarok; Mohammad Taufiq Rahman (Jurnal Iman dan Spiritualitas, 2021)
This study focuses on the dynamics of Islamic thought, which is a central issue in Indonesia. The study takes the case of Nurcholish Madjid and Abdurahman Wahid, who have a unique idea of the idea of Islamic renewal in Indonesia. These two figures have detailed conceptual formulations about futuristic thinking of Islamic reform in Indonesia. The method used in this research is qualitative, with library research involving books, commentaries, journals, papers, theses, theses, dissertations and others. Data analysis was carried out comparatively. Data analysis in qualitative research is divided into three stages: data collection, data presentation, and conclusion drawing/verification. This study finds that the concepts of Indonesian Islam and Nusantara Islam are ideas resulting from appreciation or reflection of Islam in Indonesia by elaborating Islamic values and Indonesian or Nusantara values. These two ideas play a strategic role in building relationships and collaborating on the grand narrative of Islam and Indonesia.